2017
DOI: 10.1183/16000617.0113-2016
|View full text |Cite
|
Sign up to set email alerts
|

Screening for COPD: the gap between logic and evidence

Abstract: Chronic obstructive pulmonary disease (COPD) is a common disease leading to further morbidity and significant mortality. The first step for any condition is to make the appropriate diagnosis, and spirometry barriers abound in practice around the world. It is tempting to undertake mass screening on all smokers to detect COPD. While this would pick up cases of COPD, results of studies of its effect on COPD end-points such as exacerbations, hospitalisations and mortality are disappointing. As such, aggressive cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 56 publications
1
39
0
1
Order By: Relevance
“…COPD is a highly prevalent condition that is related to smoking and old age that confers significant morbidity and mortality, and the results of the current analysis demonstrated that survivors of OPC had twice the risk of developing COPD compared with controls. NCCN guidelines recommend computed tomography scans of the chest as clinically indicated during surveillance for patients with a smoking history . In addition, screening with spirometry is inexpensive and easily performed in a primary care setting.…”
Section: Discussionmentioning
confidence: 61%
“…COPD is a highly prevalent condition that is related to smoking and old age that confers significant morbidity and mortality, and the results of the current analysis demonstrated that survivors of OPC had twice the risk of developing COPD compared with controls. NCCN guidelines recommend computed tomography scans of the chest as clinically indicated during surveillance for patients with a smoking history . In addition, screening with spirometry is inexpensive and easily performed in a primary care setting.…”
Section: Discussionmentioning
confidence: 61%
“…Secondary prevention aims to detect airway obstruction when it is still relatively mild and treatable [89]. Studies focusing on Greek primary healthcare settings reveal that COPD is mainly undiagnosed [33,[38][39][40][41]90].…”
Section: Secondary Prevention Of Copd In the Years Of Economic Crisismentioning
confidence: 99%
“…Ideally, approaches to achieve the goal of early diagnosis in COPD need a major overhaul, and a culture change is required in primary-care settings. For this reason, a higher index of suspicion, as well as wider use of spirometry for diagnosis, are proposed [33,[38][39][40][41][89][90][91]. A study conducted at the beginning of the economic recession revealed major shortages in rural primary healthcare equipment; only 4.6% of rural doctors had spirometers available for clinical use [91].…”
Section: Secondary Prevention Of Copd In the Years Of Economic Crisismentioning
confidence: 99%
“…It is argued by the data about the influence of broncholithus on heart rate, electrolytic changes. So, it is important to elaborate the simple available screening methods that allow to select patients for further functional examination with high reliability degree [11,[20][21][22]. This very aim is set in our work.…”
Section: Discussion Of Resultsmentioning
confidence: 99%